2015
DOI: 10.1111/jocs.12586
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Following Surgical Aortic Valve Replacement

Abstract: Background Acute kidney injury (AKI) is a significant complication of surgical aortic valve replacement (SAVR). This study sought to describe AKI following SAVR, its risk factors, predictors and effect on long-term survival. Methods We retrospectively reviewed 2169 patients who underwent isolated SAVR between 2000 and 2012. The main end-points were occurrence of AKI, postoperative complications, and short-and long-term survival rates following SAVR. Patients were divided into two groups: AKIR (n = 181) and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 52 publications
8
28
0
Order By: Relevance
“…[3] Patients with AKI in the postoperative period have a higher infection and sepsis rate with longer intensive care unit stay and higher mortality rate, while they need more intra-aortic balloon pump and inotropic support. [19,[22][23][24][25] Consistent with the previous findings, we found higher sepsis and postoperative atrial fibrillation rates in AKI (+) patients. Our patients with AKI also needed more intra-aortic balloon pump and renal replacement therapy during the postoperative course.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…[3] Patients with AKI in the postoperative period have a higher infection and sepsis rate with longer intensive care unit stay and higher mortality rate, while they need more intra-aortic balloon pump and inotropic support. [19,[22][23][24][25] Consistent with the previous findings, we found higher sepsis and postoperative atrial fibrillation rates in AKI (+) patients. Our patients with AKI also needed more intra-aortic balloon pump and renal replacement therapy during the postoperative course.…”
Section: Discussionsupporting
confidence: 89%
“…Considering the comorbidities, there is a number of studies showing that diabetes mellitus, chronic obstructive pulmonary disease, high body mass index, congestive heart failure, and cardiopulmonary bypass time are important factors for AKI development. [16,19] In our study, we found a higher rate of diabetes mellitus in AKI (+) group with an older age. Other preoperative comorbidities were not related with AKI in our study.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Predictors of AKI in SAVR are mainly BMI and intraprocedural transfusion (50). PARTNER, PARTNER 2A, and SURTAVI trials showed a marked lower rate of AKI in TAVR compared to SAVR at 30-day follow-up (1.3 vs. 3.1, P=0.006; 6 vs. 15.1, P<0.001 and 1.7 vs. 4.4, 95% CI: −4.4 to −1.0 respectively) that was maintained at 1 and 2-year follow-up (13,14,19).…”
Section: Bleeding and Acute Kidney Injury (Aki)mentioning
confidence: 99%